2019
DOI: 10.3390/su11102739
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Corporate Social Responsibility on Service Innovation Performance: The Role of Dynamic Capability for Sustainability

Abstract: The effects of corporate social responsibility (CSR) on product and technological innovation have been thoroughly examined. However, the relationship between CSR and service innovation remains largely unexplored. We examined the relationship between community and environmental CSR and service innovation performance, with further exploration of the mediating mechanism between them. Based on social capital and dynamic capability theory, we developed a model revealing that CSR improves the performance of service … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(64 citation statements)
references
References 108 publications
(136 reference statements)
0
61
0
3
Order By: Relevance
“…Among these variables, sustainable innovation is widely recognized and supported mediator [60]. Much attention has been paid to innovation activities, innovation capabilities, and innovation decision making [24], but innovation efficiency-and in particular the most basic element of efficiency, innovation speed-remain understudied.…”
Section: Social Capitalmentioning
confidence: 99%
“…Among these variables, sustainable innovation is widely recognized and supported mediator [60]. Much attention has been paid to innovation activities, innovation capabilities, and innovation decision making [24], but innovation efficiency-and in particular the most basic element of efficiency, innovation speed-remain understudied.…”
Section: Social Capitalmentioning
confidence: 99%
“…Some of the associated internal strategic and operational measures include learning orientation, training, regulation, market dynamism, public concern, competitive intensity, and innovation. Several studies related to CSR practices have shown a positive effect on performance and competitive advantage in SMEs [60,[64][65][66]. Importantly, attention has been given to issues related to environmental performance.…”
Section: Cluster 1: Responsible Innovation Drivers In Smesmentioning
confidence: 99%
“…Values and motivations: SMEs' motivations for responsible innovation can be manifold [6], including, for example, motivations related to cost reduction practices [22], compliance with standards [46], consumerist or instrumental matters [66], competitiveness, legitimacy, and personal commitment [75]. Based on this ideas, the awareness of the role and power of business in society, mostly based on moral and ethical arguments [32,46], i.e., doing "the right thing", that "everyone has a responsibility to do what they can", is significant, because researchers have found that it leads to the recognition of the active and primary role of employees [66]. This moral and ethical culture encourages them to perform their tasks and responsibilities in a more committed and satisfying manner [53,92].…”
Section: Reflexivenessmentioning
confidence: 99%
See 2 more Smart Citations